Repurposing Ellipticine Hydrochloride to Combat Colistin-Resistant Extraintestinal Pathogenic E. coli (ExPEC) - Lu, Hao; Liu, Manli; Lu, Wenjia; Wang, Chenchen; Wang, Gaoyan; Dong, Wenqi; Wang, Xiangru; Chen, Huanchun; Tan, Chen (Frontiers in Microbiology, 2020)
Extraintestinal pathogenic Escherichia coli (ExPEC) strains are the cause of a majority of human extraintestinal infections globally , resulting in enormous direct economic and medical costs. The plasmid-mediated colistin-resistant gene mcr-1 broken through the ultimate defense line against MDR Gram-negative pathogens. There is an urgent need to discover the new compound intended for colistin-resistant E.coli. In this study, antibacterial targets of ellipticine hydrochloride (EH) was confirmed by LSPR and decatenation assay. The LSPR analysis exhibited good binding between ellipticine hydrochloride and E.coli topoisomerase IV. The results of co-administration of EH and with colistin indicated 8 isolates (80%) displayed synergic effect, while 2 isolates (20%) showed no difference. The bacteria enumeration analysis of EH treatment group suggested that the decreased bacterial titre can be observed in various tissues of infected mice. EH treatment significantly decreased the levels of a variety of pro-inflammatory factors, such as TNF-α and IL-6. Moreover, other related lesions, such as inflammatory cell infiltration, alveolar interstitial congestion, and oedema were observed to be relieved to different extents.This study reveals the anti-E.coli potential activities and molecular mechanism of EH and the therapeutical effectiveness of EH application to animals. Its provides us with a new option for fighting against multidrug-resistant extraintestinal pathogenic E.coli infections in the future.